The determination of total calcium in urine: a comparison between the atomic absorption and the ortho-cresolphtalein complexone methods - Lucia Simas Parentoni; Ronise Carla Sass Pozeti; José Francisco Figueiredo; Eliana Cotta de Faria (Sociedade Brasileira de Patologia Clínica, 2001)
Atomic absorption spectrometry has been recommended as the reference method for the analysis of total calcium in body fluids and the ortho-cresolphtalein complexone (o-CPC) method has been widely used as the field method. We evaluated the performance of the Mega-Bayer, a fully automatic selective analyser, in determining total calcium in urine utilizing the o-CPC method. We assayed native urines with low, normal and high calcium concentrations. The two methods agreed well, according to least-squares analysis and the F-test, with Mega-Bayer having the upper limit of linearity two times higher (10 mmol/L) than that of the atomic absorption. The present method achieved excellent analytical goals and sistematic errors bellow half of the allowed limit goals recommended by the Clinical Laboratory Improvements Amendments. Final Rule. Laboratory Requirements (CLIA). We concluded that o-CPC in the Mega-Bayer equipment can confidently perform the total calcium urinary analysis with the advantage of being a fully automatized biochemical procedure and of allowing a wider linear analytical range.